Peak width of skeletonized mean diffusivity and cognitive performance in cerebral amyloid angiopathy - Horn, Mitchell J.; Gokcal, Elif; Becker, J. Alex; Das, Alvin S.; Schwab, Kristin; Zanon Zotin, Maria Clara; Goldstein, Joshua N.; Rosand, Jonathan; Viswanathan, Anand; Polimeni, Jonathan R.; Duering, Marco; Greenberg, Steven M.; et al. (Frontiers in Neuroscience, 2023)
Background: Cerebral Amyloid Angiopathy (CAA) is a cerebral small vessel disease that can lead to microstructural disruption of white matter (WM), which can be measured by the Peak Width of Skeletonized Mean Diffusivity (PSMD). We hypothesized that PSMD measures would be increased in patients with CAA compared to healthy controls (HC), and increased PSMD is associated with lower cognitive scores in patients with CAA. Methods: Eighty-one probable CAA patients without cognitive impairment who were diagnosed with Boston criteria and 23 HCs were included. All subjects underwent an advanced brain MRI with high-resolution diffusion-weighted imaging (DWI). PSMD scores were quantified from a probabilistic skeleton of the WM tracts in the mean diffusivity (MD) image using a combination of fractional anisotropy (FA) and the FSL Tract-Based Spatial Statistics (TBSS) algorithm (www.psmd-marker.com). Within CAA cohort, standardized z-scores of processing speed, executive functioning and memory were obtained. Results: The mean of age and sex were similar between CAA patients (69.6±7.3, 59.3% male) and HCs (70.6±8.5, 56.5% male) (p=0.581 and p=0.814). PSMD was higher in the CAA group [(4.13±0.94) × 10−4 mm2/s] compared to HCs [(3.28±0.51) × 10−4 mm2/s] (p<0.001). In a linear regression model corrected for relevant variables, diagnosis of CAA was independently associated with increased PSMD compared to HCs (ß= 0.45, 95% CI 0.13-0.76, p=0.006). Within CAA cohort, higher PSMD was associated with lower scores in processing speed (p<0.001), executive functioning (p=0.004), and memory (0.047). Finally, PSMD outperformed all other MRI markers of CAA by explaining most of the variance in models predicting lower scores in each cognitive domain. Discussion: PSMD is increased in CAA, and it is associated with worse cognitive scores supporting the view that disruption of white matter has a significant role in cognitive impairment in CAA. As a robust marker, PSMD can be used in clinical trials or practice.